THE INFLUENCE OF MANAGERIAL FUNCTIONS OF ROOM HEAD ON THE QUALITY OF NURSING SERVICES AT MELATI HOSPITAL - Nilawati, Nilawati (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Optimal managerial function of the head of the room is an important factor in improving the quality of nursing services. This study aims to analyze the extent to which the managerial function of the head of the room influences the quality of nursing services. The research design used a quantitative approach with simple linear regression analysis. The study population included all nurses in the inpatient room, sufficient in the ER, and less in outpatient care, with a simple random sampling technique of 45 respondents. The results showed a significant influence between the implementation of the managerial function of the head of the room on the quality of nursing services (p value = 0.000 <0.005). The implementation of the managerial function and the quality of nursing services at RSU Melati were categorized as good in the inpatient room, sufficient in the ER, and less in outpatient care. In conclusion, the better the implementation of the managerial function of the head of the room, the better the quality of nursing services.